COVID-19 Pandemic and Tourism: A Risk Management Analysis of Iran - Jamileh Ghasemloi-Soltanabad; Mirmohamad Asadi; Maryam Ahmadi-Salman (International School for Social and Business Studies, 2021)
Purpose: Tourism that inherently has human interaction and mobility is more at risk than any other industries. Because of its highly competitive nature, tourism has to be prepared to deal with problems. Study design/methodology/approach: In this developmental-applied study, the researchers tried to consider the extent of the COVID-19 pandemic as a global crisis by Fuzzy Cognitive Mapping technique (FCM). Findings: According to the findings, confidence building propaganda action plan, tax forgiveness, and payment of subsidies and support, the need to take knowledge of crisis management seriously, forming a crisis management team, and target market design are the most important strategies for overcoming the corona crisis. Originality/value: The findings of the present study may have some significant theoretical and practical implications for risk management students and experts.   Keywords: COVID-19, Crisis Pathology, Tourism Risk Management, Fuzzy Cognitive Mapping Technique (FCM)